2022
DOI: 10.3389/fcimb.2022.855731
|View full text |Cite|
|
Sign up to set email alerts
|

Mycoplasmas as Host Pantropic and Specific Pathogens: Clinical Implications, Gene Transfer, Virulence Factors, and Future Perspectives

Abstract: Mycoplasmas as economically important and pantropic pathogens can cause similar clinical diseases in different hosts by eluding host defense and establishing their niches despite their limited metabolic capacities. Besides, enormous undiscovered virulence has a fundamental role in the pathogenesis of pathogenic mycoplasmas. On the other hand, they are host-specific pathogens with some highly pathogenic members that can colonize a vast number of habitats. Reshuffling mycoplasmas genetic information and evolving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 443 publications
1
27
0
Order By: Relevance
“…The higher isolation rate of Mycoplasma was from nasal swabs 68% followed by oropharyngeal swabs 58% and conjunctival swabs 44%, whereas different results were confirmed by previous studies Barreto et al (31) and Schulz et al (33) who indicated the highest isolation rate from oropharyngeal swabs 42.86%, and agreed with him in the lowest rate of isolation from conjunctival swabs 18.30%. The high isolation rate from oropharyngeal swabs supports that Mycoplasma are normal commensals of the upper respiratory tract and when stressful conditions occurred, the Mycoplasma convert to pathogens and the clinical respiratory cases appear (34,35), and what proves that is the low isolation rates from the same swab types of normal healthy dogs (31).The high upper respiratory tract infections in current study was recorded in the young (less than oneyear aged) dogs 58.3%, While they occurred less frequently in the more-one year dogs and more frequent in diseased males 66.6% than diseased females 8.3% and mainly in Terrier and German dogs 100%, although the Mycoplasma isolation rate was higher from the swabs of the more-one year female dogs. These results were agreed with Chalker et al (36) who confirmed that there was a considerable relation between Mycoplasma cynos infection and young age <1 year, but so differed from Chan et al (37) who recorded high isolation rate of Mycoplasma from upper respiratory tract infections in age near 1.5year, also they recorded high isolation rate of Mycoplasma from upper respiratory tract infections in female more than male, and in Toy dog breed more than another breed.…”
Section: Discussionmentioning
confidence: 87%
“…The higher isolation rate of Mycoplasma was from nasal swabs 68% followed by oropharyngeal swabs 58% and conjunctival swabs 44%, whereas different results were confirmed by previous studies Barreto et al (31) and Schulz et al (33) who indicated the highest isolation rate from oropharyngeal swabs 42.86%, and agreed with him in the lowest rate of isolation from conjunctival swabs 18.30%. The high isolation rate from oropharyngeal swabs supports that Mycoplasma are normal commensals of the upper respiratory tract and when stressful conditions occurred, the Mycoplasma convert to pathogens and the clinical respiratory cases appear (34,35), and what proves that is the low isolation rates from the same swab types of normal healthy dogs (31).The high upper respiratory tract infections in current study was recorded in the young (less than oneyear aged) dogs 58.3%, While they occurred less frequently in the more-one year dogs and more frequent in diseased males 66.6% than diseased females 8.3% and mainly in Terrier and German dogs 100%, although the Mycoplasma isolation rate was higher from the swabs of the more-one year female dogs. These results were agreed with Chalker et al (36) who confirmed that there was a considerable relation between Mycoplasma cynos infection and young age <1 year, but so differed from Chan et al (37) who recorded high isolation rate of Mycoplasma from upper respiratory tract infections in age near 1.5year, also they recorded high isolation rate of Mycoplasma from upper respiratory tract infections in female more than male, and in Toy dog breed more than another breed.…”
Section: Discussionmentioning
confidence: 87%
“…The adhesion and colonization of host cells by Mycoplasma is a key step in infection. However, due to their small molecular weight, Mycoplasma species do not contain the classical bacterial toxins present in other bacteria; therefore, the virulence molecules used by M. synoviae for adhesion, invasion, and immune evasion are not fully de ned [11].…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion is the rst step in colonization during pathogen infection; therefore, bacterial adhesins can be considered promising vaccine candidates [11]. As Mycoplasma lack cell walls, membrane surface lipoproteins play an important role in the adhesion and invasion of host cells and are critical for activating the host immune response; thus, these proteins are potential vaccine candidates [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, bacteria with biofilm formation ability have higher penicillin resistance ( Boonsiri et al., 2020 ). Therefore, the elimination of biofilm plays an important role in the treatment of disease ( Dawood et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%